Informacyjne podstawy szacowania szkód ekologicznych na przykładzie oddziaływań górnictwa odkrywkowego - Graczyk, Andrzej (Informational basis for ecological damage assessment on the example of opencast mining, 2006)
The aim of the article is to present possibilities of applying information created within procedures established by Polish natural protection regulations. The first part describes the informational contents of impact assessment perceived as the basis for quantitative evaluation of the influence of opencast mining upon natural environment. In the second part, the article goes on to describe information supplied in the procedure of applying for emission pern.its and for integrated permits. The third part contains an evaluation of practical aspects of using assessment of damage to private property caused by the influence of mining upon the natural environment. The basis for evaluation is an analysis of legal solutions in this area, focusing on the type of incident involving compensatory restoration activities, as well as legally acceptable methods of compensation for the damages or calculating financial compensation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (5); 2006; nr 1115, s. 107-120